Organizational knowledge management through a corporate social media framework - Noveno, Kirsten Ann F. (University of the Philippines Diliman, 2013)
Knowledge sharing and collaboration has always been a challenge for organizations. The limitations in the communication channels, organizational values, and personal intentions are some factors that hinder the effective flow of information. The challenge not only lies on knowledge sharing and collaboration but also on how the knowledge can produce value-adding results. According to a study by McKinsey Global Institute (2012), two-thirds of the value creation opportunity afforded by social technologies lies in improving communications and collaboration within and across enterprises. To facilitate value creation, the study aims to solve this problem by creating a generic blueprint for a corporate knowledge management tool that utilizes the social media framework. Complementary organizational policies were also formulated to ensure that the tool is fully utilized to maximize value creation. Search and review of related literatures describing frameworks for knowledge management activities on an organization was performed to develop the functionalities needed for the tool. A suitable model that identifies these knowledge activities, at the same time giving emphasis on knowledge use and value creation is the Knowledge Value Creation model. Based on the model, the three components involved in knowledge value creation are input knowledge, knowledge activities and output value. Features that will handle such activities were then identified. Wireframes of the knowledge management tool are also included to provide an overall look and feel of the application. The complementary policies formulated covers resource allocation, monitoring and control, management interaction, expert's involvement, management of training needs, user access management, employee engagement and continuous improvement.